RISK FACTOR ANALYSIS OF NUTRITIONAL STATUS OF TODDLERS IN KARRANG VILLAGE ENREKANG REGENCY 2026 - Yuni Sari; Mardhatillah; Khaeriyah Adri; Nurjannah Nonci (CV. Fahr Publishing, 2026)
Child malnutrition remains a local health concern in Karrang Village, Enrekang Regency. This study examined factors related to abnormal nutritional status among toddlers aged 12–59 months, focusing on supplementary feeding, infectious disease history, maternal nutrition knowledge, and low birth weight. An analytical observational study with a matched case-control design was carried out from January to March 2026. From 79 eligible toddlers, 48 were included: 24 cases with abnormal nutritional status and 24 age- and sex-matched controls with normal nutritional status. Information was obtained through mother interviews, anthropometric assessment, and review of maternal-child health books, growth monitoring cards, and Posyandu records. Data were analyzed using Chi-square or Fisher’s exact tests, odds ratios, and 95% confidence intervals. A previous infectious disease was significantly associated with abnormal nutritional status (OR = 5.92; 95% CI: 1.387–25.300; p = 0.026). Poor maternal knowledge and low birth weight indicated elevated but statistically non-significant risks, whereas inadequate supplementary feeding showed no association. Infectious disease history was the dominant factor linked to abnormal toddler nutritional status. Therefore, infection control, timely illness management, and maternal nutrition education need to be intensified.